Methaemoglobinaemia in the perioperative period with regional block. Issue 9 (7th September 2021) - Cook, Arianna; Grant, Stuart; Kapeluk, Sharon; Steele, Patrick
Abstract : Methaemoglobin is a form of haemoglobin with oxidised ferric (+3) iron rather than ferrous (+2) iron, which causes a leftward shift in the oxyhaemoglobin dissociation curve and prevents oxygen delivery. Anaesthesiologists need to be familiar with this differential diagnosis for hypoxia given the use of drugs in the perioperative setting known to induce methaemoglobinaemia, including benzocaine and lidocaine, antibiotics such as dapsone and anaesthetic gases, including nitric oxide. This case report details an interesting case of symptomatic methaemoglobinaemia in the perioperative period in the setting of dapsone use and an erector spinae block performed with ropivacaine.